Psychometric Challenges in the Measurement of Constructs Underlying Criminal Responsibility in Children and Young Adults: A Cross-Sectional Study - Shang, Yuxi; Fu, Yumiao; Ma, Beibei; Wang, Li; Wang, Dexin (Frontiers in Psychology, 2022)
At present, many countries have lowered the minimum age of criminal responsibility to deal with the trend of juvenile crime. In practical terms, whether countries advocate for lowering the age of criminal responsibility along with early puberty, or regulating the minimum age of juvenile criminal responsibility through their policies, their deep-rooted hypothesis is that age is tied to adolescents’ psychological growth, and, with the rise in age, the capacity for dialectical thinking, self-control, and empathy gradually improves. With this study, we aimed to test whether this hypothesis is valid. The participants were 3,208 students from junior high school, senior high school, and freshman in the S province of the People’s Republic of China (PRC). We subjected the gathered materials to independent-samples t-tests, one-way analysis of variance (ANOVA), linear regression analysis, and Bonferroni post hoc test. The influence of the age variable upon dialectical thinking, self-control, and empathy was significant (p = 0.002, p = 0.000, p = 0.072), but only empathy was positively correlated with age variable (B=0.032); dialectical thinking ability (B=-0.057) and self-control ability (B=-0.212) were negatively correlated with the age variable. Bonferroni post hoc test confirmed these findings. Therefore, we concluded the following: (1) Juvenile criminal responsibility, based on the capacity for dialectical thinking, self-control, and empathy, are not positively correlated with the age. (2) Age is not the only basis on which to judge a juvenile’s criminal responsibility. (3) More research that directly links age differences in brain structure and function to age differences in legally relevant capacities and capabilities(e.g., dialectical thinking, self-control, and empathy) is needed.(4) Political countries should appropriately raise the minimum age of criminal responsibility and adopt the doli incapax in the judicial process.